Encapsulated cell biodelivery of NGF (ECB‐NGF) for AD therapy has implications from astroglial activation and amyloid‐beta toxicity: Nonhuman/Lead optimization studies. (7th December 2020) - Mitra, Sumonto; Turchetto, Silvia; Wahlberg, Lars; Linderoth, Bengt; Behbahani, Homira; Eriksdotter, Maria
Abstract: Background: Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterised by loss of cholinergic neurons in the basal forebrain (BFCN). Mature Nerve growth factor (mNGF) is required for the survival of BFCN's, but since it cannot cross blood‐brain barrier (BBB), its tissue targeted delivery via encapsulated cell biodelivery (ECB‐NGF) device has been envisaged as a potential therapeutic strategy. In our previous first‐in‐human studies, we observed some inter‐capsule differences in mNGF release among ECB‐NGF devices, when implanted in human AD patients. To address this issue, we pursued whether amyloid‐beta (Ab40/42 ) peptides directly or indirectly (by activating astroglial cells) can affect the NGF‐delivering (NGC‐0211) cells. Method: We tested direct or astrocyte‐mediated (indirect) effect of Ab40 and Ab42 on the NGC‐0211 cells in‐vitro . To study the astrocyte‐mediated effects of Ab peptides, human primary astrocytes were first incubated with Ab peptides and the conditioned medium was further transferred on NGC‐0211 cells. Effects on cell survival (flowcytometry), stress markers (spectrophotometric measurements), cell proliferation (immunocytochemistry) and NGF release (ELISA) were monitored. Result: We report that Ab‐peptides induced marginal effects on cell survival and NGF release upon direct and indirect stimulation. Astrocyte conditioned media partially modulated biochemical parameters. In both cases of stimulation method, cell proliferative ability of NGC0211 cells was significantly hampered. Conclusion: Our data suggests that the survival of the NGC‐0211 cells is not affected by Ab peptides, whereas their proliferation was significantly hampered, directly as well as through astroglial activation. Overall, NGF release was not affected negatively under the conditions and time points tested in this study. This study lays the foundation for further optimization of ECB‐NGF devices for future AD therapy.